Physicochemical and Sensory Characteristics of Rose-Spices Drink with Red Ginger, Lemongrass, and Cinnamon Extract as Functional Beverage - Elfi Anis Saati; Edwin Eka Haprinata; Sri Winarsih; Mochammad Wachid; Vritta Amroini Wahyudi (Universitas Dr Soetomo, 2021)
Rose flower has varieties of compounds, one of that is antioxidants, but it's not been widely used in the food sector. The processing that can be applied to roses is to make them for functional drinks by adding variations of the three spice filtrate, which are expected to increase the quality, characteristics and increase the antioxidant activity of the product. This study aims to determine the interaction between the type of spice filtrate and the concentration of the spice filtrate to the quality of the Rose-Spices Drink. Randomized block design (RBD) with 2 replications. The best treatment for Rose-Spices Drink was P4K1 (Spice Combination: 5%) with antioxidant activity 89.67%, brightness level (L) 32.7, redness level (a+) 2.7, yellowness level (b+) 4.1, pH 4.053, total dissolved solids (TDS) 11.7 °Brix, total anthocyanin 0,20 mg/L, taste 3.60 (quite like ), flavor 3.50 (quite like) and preference 3.23 (quite like).